Safety and practice for organic food - Biswas, Debabrata; Micallef, Shirley A. (London Academic Press, an imprint of Elsevier, 2019)
Safety and Practice for Organic Food covers current food safety issues and trends. It provides detailed information on all organic and pasture practices including produce-only, farm-animal-only, or integrated crop-livestock farming, as well as the effect of these practices on food safety and foodborne infections. The book explores food products that organic, integrated, and traditional farming systems contribute to consumers. As the demand for organic food products grows faster than ever, this book discusses current and improved practices for safer products. Moreover, the book explores progressive directions, such as the application of next-generation sequencing and genomics to aid in the understanding of the microbial ecology of the agrienvironment, and how farmer education can contribute to sustainable and safe food--back cover.
Includes bibliographical references and index.
Keywords: Natural foods -- Quality control -- Handbooks, manuals, etc; Natural foods -- Safety measures -- Handbooks, manuals, etc